"DEEP THE RAVEN WADES IN GORE:" DEATH SONGS AND THE NORSE-GOTHIC SPECTACLE. - Sharon Choe (Litteraria Pragensia: Studies in Literature & Culture, 2025)
The Norse skaldic poem The Death Song of Ragnar Lodbrok, a celebration of the military exploits and death of the legendary warrior-king Ragnar Lodbrok, was a popular text for translation in the eighteenth century. In the early part of the period, the barbaric ancient North was set in opposition to the refined Classical world, but by the late eighteenth century the Nordic landscape was recast as a place of Gothic liberty, and the Norseman as a familiar Other. Translations of The Death Song increasingly presented Ragnar's violent exploits and fearless death in a snake pit as a spectacle of heroism, especially when the Norse-Gothic became integrated into England's search for an ethnic literary past to counter the rising Celticism post-Ossian. However, despite revising the Nordic martial spirit into a symbol of resistance against tyranny, English translations of Norse narratives continued to present shocking visuals for the British public, where tales of terror and extraordinary courage were packaged in gory visions of Viking warmongering. This article compares three influential translations of The Death Song: by Thomas Percy (1763), Hugh Downman (1781), and James Johnstone (1782). The article examines how their presentation of gory spectacle reworks Viking death-defiance into a British, specifically English, trait, thus transforming Ragnar's exploits into a prototype of resistance and "necropower." Death is reimagined within modes of political sovereignty via the shocking aesthetics of Norse-Gothic terror.